Effects of Internship Experience and Organizational Activity on Job Readiness Mediated by Self-Efficacy: Examining 2021 FEB UNDIP Students - Josua, Randy Victor; Lataruva, Eisha (Faculty of Economics and Business | Universitas Diponegoro, 2025)
This study examines the effects of internship experience and organizational activity on job readiness, with self-efficacy serving as a mediating variable among undergraduate students of the 2021 cohort at the Faculty of Economics and Business, Diponegoro University. Using quantitative design, data were collected from 200 respondents through a validated questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS. The results show that both internship experience and organizational activity have significant positive effects on job readiness. In addition, self-efficacy is found to significantly mediate the influence of internship experience and organizational activity on job readiness. These findings indicate that practical exposure and active organizational engagement contribute not only to the development of skills and attitudes but also to the strengthening of students’ belief in their own capabilities, which in turn enhances their readiness to enter the workforce. The study provides theoretical contributions to employability research and practical insights for higher education institutions in improving student job readiness.